Kajian Faktor-Faktor Yang Mempengaruhi Produktivitas Tenaga Kerja Proyek Konstruksi - Novelia Putri Angelica; Veronika Happy Puspasari (Jurnal Basement : Jurnal Teknik Sipil, 2024)
A construction project is a series of activities carried out with limited time and resources to achieve certain goals. In the implementation of a construction project always requires resources, namely human resources, materials, machinery, money and methods. Human resources are one of the most influential factors in a job, including in a construction job. The success of the construction project as a whole depends on the success of each job in the project, while one of the factors that affect the success of a job is its work productivity. The labor of foremen, head builders and fitters are the front line that is directly related to the production process. Good labor productivity is very much needed for the success of construction projects. Lack of attention to labor productivity in a construction project can hamper the construction work itself. This article aims to determine the factors that affect labor productivity in construction projects. The method used is a literature study on factors affecting labor productivity in construction projects, by comparing several related journals. The results show that there are 7 factors that affect the labor productivity of construction projects, namely: level of education, experience, discipline, motivation, wages, age and management.